2008
DOI: 10.1063/1.2978211
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and simulation of the compositional evolution of Ti–B thin films deposited by sputtering of a compound target

Abstract: The evolution of the coating stoichiometry with pressure, target-substrate distance, and angle was analyzed for dc sputtering of TixB (x=0.5, 1, 1.6) compound targets by elastic recoil detection analysis. For an investigation of the underlying fundamental processes primarily Ar was used as sputter gas. Additionally, the effect of a reactive gas (N2) as well as bias voltage (floating up to −200 V) was briefly cross-checked. For deposition along the target normal (90°) a pronounced Ti-deficiency of up to 20% is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
57
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 44 publications
11
57
1
Order By: Relevance
“…113. The same effects were demonstrated recently by combined experimental and simulation studies by Neidhardt et al [121] for sputtering from Ti-B targets of several compositions. These results also provide a possible reason for the apparent differences between sputtering from Ti 2 AlC and Cr 2 AlC targets [98,110,111], namely that the emission characteristics of the elements may vary depending on the target.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…113. The same effects were demonstrated recently by combined experimental and simulation studies by Neidhardt et al [121] for sputtering from Ti-B targets of several compositions. These results also provide a possible reason for the apparent differences between sputtering from Ti 2 AlC and Cr 2 AlC targets [98,110,111], namely that the emission characteristics of the elements may vary depending on the target.…”
supporting
confidence: 59%
“…The results from Ti-B [121] and Ti 3 SiC 2 targets [113] are highly relevant not only to sputtering from MAX-phase targets, but to sputtering from any compound targets, especially those with large mass differences between the target constituents (e.g., most borides, carbides, nitrides, and oxides).…”
mentioning
confidence: 99%
“…We have seen the same excess of C when sputtering from a Ti 3 SiC 2 compound target [12] and it was explained by the gasphase scattering processes in combination with the angular and energy distribution of the sputtered species. This explanation is supported by Neidhardt et al [23] who showed that when sputtering from Ti-B compound targets, the film composition is dependent on both the emission characteristics, and individual scattering processes. On the other hand the effect of bias, target constitution, and gas-type was reported to be moderate.…”
Section: Thin Film Characterizationsupporting
confidence: 71%
“…Simulations of the sputter process from a compound target were performed following Mahieu et al (2006) and Neidhardt et al (2008). The initial energetic and angular distributions of the sputtered particles at the target position were simulated using TRIDYN (Mö ller et al, 1988).…”
Section: Simulations Of the Sputter Processmentioning
confidence: 99%
“…Similarly to TiC, VC can form two separate phases during the deposition, VC 1-x in cubic rock salt structure and amorphous carbon (a-C) (Pflü ger et al, 1984;Stü ber et al, 2002;El Mel et al, 2010). This phase composition is important for the mechanical properties of the coating, but depends strongly on the growth conditions (Liao et al, 2005;Eklund et al, 2007;Neidhardt et al, 2008;Zhang et al, 2013). Two important growth parameters are DC power (x5.1) and working gas pressure (x5.2).…”
Section: Introductionmentioning
confidence: 99%